Dampak Teknologi Informasi Mengenai Proses Audit: Teknologi Informasi - Carina Serly Saputri; Zulkarnain Zulkarnain (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to explore the impact of Information Technology (IT) on the audit and internal control processes of an organization. The research method employed is a literature review, involving the collection of data from various sources such as books, scholarly journals, and other references related to the research topic. After data collection, an interaction analysis is conducted, comprising data reduction, data presentation, verification, and drawing conclusions. The results of the analysis indicate that the use of IT has a significant impact on the internal control of an organization. Information technology plays a crucial role in enhancing the efficiency of the audit process through faster data collection, more accurate data analysis, and more systematic report presentation. Furthermore, information technology also enables the improvement of data validity through techniques such as triangulation and increased diligence. Thus, this research provides new insights into the role of information technology in the audit and internal control processes, highlighting the importance of considering the positive impact of IT in enhancing the efficiency and validity of audit processes.